Demokratisasi Pendidikan Islam Perspektif Nurcholish Madjid Analitis Kritis Di Era Revolusi Industri 4.0 - Ahmad Hanafi; Sutardjo Atmowidjoyo (SAP (Susunan Artikel Pendidikan), 2026)
This study examines the democratization of Islamic education from the perspective of Nurcholish Madjid using a critical analytical approach in the era of the Industrial Revolution 4.0. Traditional, dogmatic Islamic education must transform by prioritizing democratic values ​​such as freedom of thought, participation, and equality. The research objective is to integrate democratic principles into the curriculum, teaching methods, and governance of Islamic education. The focus is on the development of humanistic, inclusive, and progressive education in response to modern challenges and technological developments. The research method is a literature study through an analysis of Nurcholish Madjid's works and related literature. The results of the study indicate that the democratization of Islamic education according to Nurcholish Madjid emphasizes the principles of freedom of thought, equal access to education, respect for plurality, and the integration of Islamic values ​​with modern rationality and science. In the context of the Industrial Revolution 4.0, this thinking is relevant to encourage the transformation of Islamic education that is adaptive to technology without losing its ethical and spiritual orientation.